Functional Outcome in Elderly Patients after Hip Surgery (Journal of Pakistan Orthopaedic Association, 2013)
INTRODUCTION The incidence of hip fracture is increasing due to the ageing population. The worldwide annual number of hip fracture is estimated to rise form 1.7 million in 1990 to 6.3 million in 20501. Most of hip fracture are associated with increase mortality and morbidity that usually result in costly hospitalization and lengthy rehabilitation rehabilitation procedure. Most of the patients are unable to achieve to their pre-fracture living situation and complete functional recovery2. Our focus was proximal femur fracture in elderly population. Fracture of proximal femur remains one of the most common and potentially devastating injuries with significant morbidity and mortality among the elderly population. The present study was conducted to evaluate ambulatory capability and functional outcome in elderly patients who sustained a proximal femur fracture and underwent surgical intervention.Key words: Elderly patients, proximal hip fracture, Post-operative functional outcome.